Controlling Illicit Teak Smuggling Across the State Border through Multipronged Strategy - A Case Study of Sironcha Forest Division, Maharashtra, India - Shukla, Prabhu Nath; Mishra, Virendra Kumar (Indian Forester, 2019)
Sironcha forest division located in Maharashtra State, India suffers from interstate illicit teak smuggling. Share of the Sironcha in State's total revenue loss due to this activity was 50.8% during 2011. Devising strategies at local level shifted the dynamics in favor of forest department which resulted into drastic reduction in the timber smuggling (∼75%) during 2014 compared to 2011. Pressure over smugglers resulted into surrender of 312 smugglers during 2014. Teak seized from Godavari and Pranhita river bank was 105.76 m3 during 2014 which came to 4.18 m3 in 2015. Besides, the decrease was ∼88% and ∼95% in Sironcha and Asarali forest areas, respectively. During 2015, no such offence was registered in 12 villages. Besides, no case of case of attack of smugglers over forest staff was reported during 2015. It suggests that if multipronged strategy is devised, timber smuggling across the state border can be tackled.